Repurposing an endogenous degradation domain for antibody-mediated disposal of cell-surface proteins - Schmitt, Janika; Poole, Emma; Groves, Ian; Owen, David J.; Graham, Stephen C.; Sinclair, John; Kelly, Bernard T. (EMBO reports, 2024)
The exquisite specificity of antibodies can be harnessed to effect targeted degradation of membrane proteins. Here, we demonstrate targeted protein removal utilising a protein degradation domain derived from the endogenous human protein Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9). Recombinant antibodies genetically fused to this domain drive the degradation of membrane proteins that undergo constitutive internalisation and recycling, including the transferrin receptor and the human cytomegalovirus latency-associated protein US28. We term this approach PACTAC (PCSK9-Antibody Clearance-Targeting Chimeras).